2019
DOI: 10.5114/pm.2019.90376
|View full text |Cite
|
Sign up to set email alerts
|

A randomised-controlled trial pilot study examining the effect of pelvic floor muscle training on steroid hormone concentrations in elderly women with stress urinary incontinence

Abstract: Introduction: In this study, we attempted to examine the effect of pelvic floor muscle training on testosterone and cortisol concentrations in elderly women with stress urinary incontinence.Material and methods: The number of participants included in the analysis was 59: 30 women in the experimental group (EG) and 29 women in the control group (CG). The EG underwent pelvic floor muscle training, whereas the CG did not receive any therapeutic intervention. In the present study the authors measured testosterone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…108 Similarly pelvic floor exercises have been shown to reduce circulating levels of cortisol and may be beneficial for patients with urge incontinence as well as stress urinary incontinence. 109…”
Section: Treatments For Luts Induced By Chronic Stressmentioning
confidence: 99%
“…108 Similarly pelvic floor exercises have been shown to reduce circulating levels of cortisol and may be beneficial for patients with urge incontinence as well as stress urinary incontinence. 109…”
Section: Treatments For Luts Induced By Chronic Stressmentioning
confidence: 99%
“…37 Obesity is a triggering factor for urinary incontinence by causing intra-abdominal pressure increase, intra-vesical pressure increase and urethral hypermobility. 3 In the literature, it was shown that individuals who exercise regularly have less weight problems, stronger pelvic floor muscles and less urinary incontinence. 3 Weber Rajek et al detected that pelvic floor exercises in obese women stimulate myokine synthesis leading to muscle growth and hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…3 In the literature, it was shown that individuals who exercise regularly have less weight problems, stronger pelvic floor muscles and less urinary incontinence. 3 Weber Rajek et al detected that pelvic floor exercises in obese women stimulate myokine synthesis leading to muscle growth and hypertrophy. 3 In our study, the patient groups had obesity, and GH enlargement indicating a possible pelvic floor muscle damage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations